The Role of Counseling in the Socio-Economic Empowerment of Livestock Farmer Groups (Case Study of Livestock Farmer Groups in Dukuhbadag Village, Cibingbin District, Kuningan Regency) - Ratu Randang, Andrian (Jurnal Agrosci, 2023)
Counseling has been around since 1980, the method used is the method counseling period, but penyuluh an is considered less effective, the government adopted a policy perform the method of group counseling to guide the farmers to make the farmer group and its chairman was chosen by the farmers who are no areas these, and through group counseling livestock will be easier to record the farmers to be given counseling, this way is called a micro extension methods. Changes perceived breeders can be viewed prior to the entry of counseling and after the inclusion of counseling.The research location in the village Dukuhbadag District of Cibingbin District Brass, research was conducted in November to December 2016, through the consideration that once in shape for farmer group in the village of Dukuhbadag District of Cibingbin District Brass changes perceived livestock farmers, especially members in nauingi farmer group , as well as the effort - an effort to optimize the role of counselors in assisting farmer group.